EXPLORING SANTOONâS CUSTOMERSâ PREFERENCES THAT AFFECT THEIR PURCHASE DECISION FOR BUYING FASHION PRODUCTS - Luthfiyya Wibowo, Amira
In this digital era, there is a notable shift towards online shopping, particularly in the fashion industry. Despite this trend, Santoon, a clothing brand in Indonesia, faces challenges with significantly lower online sales compared to offline sales, even though a substantial portion of Santoon's customers and target market prefer purchasing fashion products online. This study aims to identify the preferences of Santoon's customers that affect their purchase decisions for buying fashion products. The research adopts a qualitative approach, utilizing semi-structured interviews to gather detailed insights. The sampling technique used is non-probability purposive sampling, focusing on both Santoon's past customers and its target market. This research is conducted to provide actionable insights to enhance Santoon's online presence and align its marketing strategies with customer preferences. The findings reveal that design, quality, and sizing are the most important factors that influence the customers’ preferences towards buying fashion products. Additionally, detailed product descriptions and customer reviews play a crucial role in influencing online shopping preferences. While in certain situations, customers prefer to visit offline stores to physically see and sample the products, the final purchase decision is often made online. These findings highlight the importance of improving the detail of online product descriptions and leveraging customer reviews to build trust. Moreover, integrating online and offline shopping experiences can cater to hybrid customer behavior.The actionable recommendations for Santoon include enhancing the detail and accuracy of online product descriptions, leveraging customer reviews to build trust, and integrating the online and offline shopping experiences to cater to hybrid customer behavior. Additionally, the research suggests Santoon should optimize its use of Instagram with posting contents such as daily use of santoon’s products for targeted marketing, given that a significant portion of Indonesian Instagram users fall within their target market demographic.